PROCESSING QUALITY OF SELECTED POTATO (SOLANUM TUBEROSUM L.) CULTIVARS GROWN IN RWANDA - NDUNGUTSE, VEDASTE (Potato Journal, 2019)
The aim of this study was to investigate processing quality of ten potato cultivars grown in Rwanda and their potential utilization in food products. Potatoes were grown in Busogo farm in 2016/17. Specific gravity (SG), dry matter (DM), starch and sugars were analyzed. There was a significant difference in all studied parameters at (P < 0.05). Specific gravity ranged from 1.075 for Kigega to 1.099 for Kinigi. Dry matter ranged from 20.45% for CIP392617.54 to 25.93% for Kirundo. Starch content was 14.33% for CIP392617.54 to 19.28% for Kirundo on Fresh Weight Basis (FWB). There was a significant positive correlation among SG, DM and starch. Reducing sugars were 0.10% for Kirundo and Sangema to 0.20% for Mabondo, non-reducing sugars ranged from 0.16% for Kirundo to 0.35% for Mabondo and total sugars from 0.26% for Kirundo to 0.55% for Mabondo on FWB. Most of tested varieties/clones have high DM and low reducing sugars and are suitable for processing into fried and dehydrated products. Kigega and CIP392617.54 are more suitable for boiling.